2000
DOI: 10.1046/j.1365-2362.2000.00580.x
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase activity in two healthy populations with differing rates of coronary heart disease

Abstract: Our results thus provide further support for the hypothesis that populations at increased CHD risk have diminished serum PON1 concentration and an increased prevalence of the R allele of PON1. They are also consistent with reports that the ability of PON1 to hydrolyse paraoxon is inversely related to its capacity to hydrolyse lipid-peroxides, and thus to its antiatherogenic action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
6

Year Published

2000
2000
2010
2010

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 25 publications
3
56
0
6
Order By: Relevance
“…It is possible that subjects from Northern Ireland have lower paraoxonase concentration, as lower HDL concentration could result in lower enzyme mass, but higher specific enzyme activity, i.e. higher activity per unit enzyme, in agreement with the MONICA study [14].…”
Section: Paraoxonase Activity In France and Northern Irelandsupporting
confidence: 75%
See 3 more Smart Citations
“…It is possible that subjects from Northern Ireland have lower paraoxonase concentration, as lower HDL concentration could result in lower enzyme mass, but higher specific enzyme activity, i.e. higher activity per unit enzyme, in agreement with the MONICA study [14].…”
Section: Paraoxonase Activity In France and Northern Irelandsupporting
confidence: 75%
“…However, the MONICA study [14] demonstrated that paraoxonase activity was significantly higher in Belfast compared with Toulouse, a finding at odds with those of the PRIME study. One explanation for this difference is that the populations are not directly comparable; approximately 50% of the MONICA populations were female.…”
Section: Paraoxonase Activity In France and Northern Irelandmentioning
confidence: 82%
See 2 more Smart Citations
“…O segundo polimorfismo, na região codificadora do gene da PON, ocorre na posição 55 do gene e afeta, de modo menos intenso e independente quanto ao polimorfismo PON1 192, a atividade da enzima no plasma Mackness et al, 2000). Sabe-se que a presença do alelo 55M está associada à alteração nas concentrações séricas e à baixa eficiência da PON1 plasmática (Costa et al, 2005).…”
Section: Pon1 E Hdlunclassified